RANCANG BANGUN PROTOTIPE MESIN PEMOTONG PLAT BESI DUAL AXIS BERBASIS ESP-32 TERINTEGRASI APLIKASI SMARTPHONE - Raihan Zhifhanur Muhammad; Mochammad Rusli; Bambang Siswojo (Jurnal Mahasiswa TEUB, 2023)
Iron plates in the industry must go through a forming process such as cutting before being used as needed. One of the machines that can be used in cutting iron plates is CNC (Computer Numerical Control). However, the cost of CNC is quite expensive that small industries in particular cannot afford to use these machines. The purpose of this research is to design a prototype dual axis iron plate cutter that uses the ESP-32 microcontroller as a control center that can integrate with the RemoteXY application on a smartphone. This research will be carried out by designing the assembly of electronic sub-components supporting the system, designing the microcontroller algorithm, and designing the RemoteXY application that is used to communicate with the system. Based on the test, the design of the tool made complies with the expected specifications where the tool is able to simulate cutting iron plates in line shapes with automatic or manual modes. On the rotary encoder, the distance reading error was 0.577% for X axis and 0.7109% for Y axis. Both motors are able to function properly with a load voltage close to 50% of the 17-volt input voltage, namely 6.764 volts with load and 8.586 volts without load For the X axis and 7.07 volts with load and 8.515 volts without load for the Y axis. the input and output circuits can work as they should to receive input and control the output. The user interface used using RemoteXY also works well in accepting input, managing output, and using all the features created. Keywords: ESP-32, RemoteXY, Iron Plate, Rotary Encoder, DC Motor